PKM Pelatihan Kosakata Bahasa Inggris melalui Media Audio-Visual bagi Santri di Asrama Excellent Language Organization [EXO] MAN 1 Probolinggo - Mochlis Ekowijayanto; Tiara Ainur Rizki; Siti Kholilatul Jannah; Sheila Rohmaniyah; Nurlailiya Fitriana; Rozanatul Hamimah Fauzi; Munisa Imamah (Universitas Nurul Jadid, 2021)
English learning from conventional ways to technology-based learning is well known today. It is necessary to know the efforts to use technology against the performance of students. One of the technologies that are currently popular is audio-visual. This training activity aims to improve the vocabulary of students after learning English using audio-visual. The participants of this training are students who live in the excellent language organization [EXO] MAN 1 Probolinggo dormitory. The results of this training activity are expected to provide motivation for students in the use of audio-visual media and can increase a high sense of learning interest and improve vocabulary mastery in English.